Characteristics of raw water sources and analysis of the optimal model of the mixing process with parameter design in clean water pump installations - Tamjidillah, Mastiadi; Ramadhan, Muhammad Nizar; Setiawan, Muhammad Farouk; Iberahim, Jerry (Eastern-European Journal of Enterprise Technologies, 2021)
The quality characteristics of raw water sources in the regional integrated drinking water supply system (SPAM) of Banjarbakula were investigated and found to maintain the supply of drinking water quantity and quality in accordance with drinking water standards. The optimum model for the mixing process of raw water and poly aluminum chloride (PAC) and pump stroke for the input of water sources from rivers to obtain a composition setting that is in accordance with the raw water sources of each region in the region was selected and determined. So the optimum parameter setting model between alum water, raw water and pump stroke for each raw water source is known and is regionally integrated as a result of a comprehensive study. The integration of Taguchi parameter design and response surface can complement each other and become two methods that go hand in hand in the process of optimizing clean water products. Parameter design provides a very practical optimization step, the basis for this formation refers to the factorial fractional experimental design. However, the absence of statistical assumptions that follow the stages of analysis makes this method widely chosen by researchers and practitioners. With the experimental design of the raw water mixing process, turbidity such as 5 lt/sec, 10 lt/sec, 15 lt/sec, 20 lt/sec and 25 lt/sec and % PAC concentration 5 ppm, 10 ppm, 15 ppm, 20 ppm and 25 ppm with a pump installation stroke of 5 %, 10 %, 15 %, 20 % and 25 % were used. In the process of adding PAC, always pay attention and observe the behavior of the attractive force of the floating particles (flock). The particles were then subjected to SEM (scanning electron microscopy) to determine the dimensions of the flock grains deposited